Collaboration and Creative Autonomy: AI in the Process of Creation in Art and Design - Beatriz Costa do Nascimento; Suzete Venturelli (ANIAV)
This article investigates the role of Artificial Intelligence (AI) as a collaborator in the creative process in art and design, especially in computational generative creation. With the advancement in the complexity of AI tools, the possibility of machine-human co-authorship arises, where the code actively participates in creative decisions and directly impacts the result. We explore how AI and programming tools can act beyond technical support, taking on a more autonomous role and offering new paths for creation. The study also considers ChatGPT as an auxiliary tool for learning and solving problems in creative programming, highlighting its potential and limitations. It is important to highlight that Artificial Intelligence will be used during the process of developing and editing programming codes and not as an image creation agent itself. Therefore, important questions about the appropriation of artists' images and identities by AI will be discussed at another time. The research, developed in the Postgraduate Program in Design at Anhembi Morumbi University seeks to expand understanding of the relationships between art, technology and creative autonomy, contributing to the interdisciplinary debate in the field of contemporary design.